Maternal Oxygen Transport Capacity and Nutritional Reserves: Anemia and Mid-Upper Arm Circumference (MUAC) as Independent Predictors of Low Birth Weight in the Indonesian Highlands - I Putu Adigama; I Nyoman Sayang; Gusti Ngurah Nyoman Yuliastina; I Made Pasek Soma Gauthama (Community Medicine and Education Journal, 2026)
Low birth weight (LBW) remains a critical determinant of neonatal mortality and long-term metabolic syndrome, particularly in agrarian transition zones. While demographic factors are often studied, the specific impact of maternal oxygen transport capacity (hemoglobin) and somatic nutritional reserves (Mid-Upper Arm Circumference/MUAC) remains under-characterized in highland populations where the paradox of food security versus nutritional insecurity exists. A retrospective case-control study was conducted in the highland region of Bangli, Indonesia, covering all deliveries in 2024. To maximize statistical power within the available clinical population, a total sampling technique was employed for the case group (n=20 mothers delivering infants <2,500g), matched 1:2 with randomly selected controls (n=40 mothers delivering infants ≥2,500g). Data were analyzed using independent t-tests and binary logistic regression. The multivariate model was restricted to biological predictors to maintain statistical stability given the sample size. The prevalence of anemia and Chronic Energy Deficiency (CED) was significantly higher in the case group (p<0.001). Bivariate analysis indicated profound risks associated with anemia (OR=9.00) and CED (OR=6.93). In the adjusted multivariate model, maternal anemia (aOR=11.45; 95% CI: 2.50–52.40) and CED (aOR=9.80; 95% CI: 2.15–44.60) remained dominant, independent predictors. The wide confidence intervals reflect the small sample size inherent to the facility-based dataset. ROC analysis demonstrated that MUAC <23.5 cm offers excellent diagnostic accuracy (AUC=0.845). In conclusion, clinical markers of oxygen transport and nutritional substrate availability are superior predictors of LBW compared to maternal age or parity in this cohort. The findings advocate for a biological-first approach to antenatal risk stratification.